EVALUATION OF CUSTOMER EXPERIENCE IN TERMS OF OMNI CHANNEL MANAGEMENT (Third Sector Social Economic Review, 2022)
As consumer demands and needs change with the developments in technology, businesses need to be dynamic in order to adapt to these changes. Since businesses adapt their business processes to these innovations and all their products and services are accessible, providing uninterrupted service in order to create a competitive advantage is the focus of businesses. As a result of all these developments, omni-channel management has emerged. The main purpose of this study is to discuss the importance of omni-channel practices adopted by businesses in their distribution channels, their effects on customer experience within the scope of literature and within the framework of marketing activities of businesses. The study basically aims to reveal the importance of the omni-channel experience as a result of the literature review and the knowledge of how omni-channel management is used.
Keywords: Omni-Channel; Customer Experience; Customer Journey Map